Design and Integration of a Gas Sensor Module that Indicates the End of Service Life of a Gas Mask Canister. Issue 3 (16th October 2021) - Moon, Seung Min; Lee, Seongwoo; Min, Hyegi; Park, Sanghwan; Yoon, Sook; Choi, Jae Hong; Yoon, Soon Min; Jung, Byeongyun; Im, Taehyun; Jeong, Chan‐seok; Kim, Beomjin; Lee, Chang Young
Abstract: In a filtration system, a chemical cartridge packed with porous adsorbents needs to be replaced when its maximum adsorption capacity is exceeded. An end of service life indicator (ESLI) informs when to replace the cartridge. However, ESLI technology for filtration of toxic gases is overlooked despite high toxicity of the gases even at low concentrations. In this study, a real‐time ESLI is demonstrated for filtration of chemical warfare agents by inserting four chemiresistors made of carbon nanotubes into the adsorbent layer of a canister for gas masks. The sensors are installed on a flexible printed circuit board with a 3D structure to minimize the channeling effect in the canister. As the breakthrough of dimethyl methylphosphonate, a nerve agent simulant, progresses in the canister, the resistance of the sensors increases sequentially with time. The inflection points in the responses from sensors designated #1–#4 indicate that the percentage of remaining service life is 75%, 50%, 25%, and 0%, respectively. The ESLI potentially applies to a wide range of toxic gases and cartridge designs, regardless of the sensitivity and selectivity of the sensors, as supported by the breakthrough of ammonia as well as the results from a smaller canister. Abstract : The design of a sensor module that indicates the end of service life of a gas mask canister is presented. Gas sensors inserted into the adsorbent layer of the canister respond sequentially as the breakthrough of a toxic gas progresses, showing close correlation with the remaining service life of the canister.